Support Vector Machines - Deng, Naiyang; Tian, Yingjie; Zhang, Chunhua (Chapman and Hall/CRC, 2012)
Support Vector Machines: Optimization Based Theory, Algorithms, and Extensions presents an accessible treatment of the two main components of support vector machines (SVMs)-classification problems and regression problems. The book emphasizes the close connection between optimization theory and SVMs since optimization is one of the pillars on which.
Online resource; Title from title page (viewed December 17, 2012)
Keywords: Mathematical optimization; Support vector machines; Machines à vecteurs supports; Optimisation mathématique